KONSEP HIJAB DALAM ISLAM - Qasthalani, M. (JURNAL NIZHAM, 2014)
Philosophy behind the use of hijab on Women is that women must cover her body to prevent the wrong sights of man toward women, and women should not show her body off to men who are not their muhrim. This rule has been asserted by Qur.an and sunnah as the source of Islamic law. Qur.an in surah al-Ahzab and Al-Nur when stating this rule that is regulating the boundaries relation between men and women does not refer specifically to the word hijab and the word hijab specifically used only when it is referring to the wives of Muhammad.Keywords: Muslim clothing, Mahram, Genitalia